Synthesis and characterization of newly developed phosphate-based glasses through experimental gamma-ray and neutron spectroscopy methods: Transmission and dose rates - Kavaz, Esra; Ersundu, Miray Celikbilek; Ersundu, Ali Ercin; Tekin, H. O. (ELSEVIER SCI LTD, 2022)
In this study, four new phosphate-based glasses with the compositions of CaO-Na2O-K2O-P2O5 (PN system), CaO-Na2O-K2O-Al2O3-P2O5 (PA system) and CaO-Na2O-K2O-Al2O3-SiO2-P2O5 (PS system) were synthesized and characterized through experimental gamma-ray and neutron spectroscopy methods. Glass densities were then measured experimentally and evaluated theoretically. Next, a high purity Germanium (HPGe) detector was used for determining the fundamental gamma-ray transmission parameters in 35.4-383 keV gamma-ray energies emitted from 133Ba source (Radioactivity: 3Ci). Additionally, the experimental setup was used to determine the equivalent dose (EAD) to get a better knowledge of fast neutron attenuation. Our findings indicate that experimental gamma-ray transmission measurements are consistent with standard theoretical data (EpiXS). Consequently, PA10 was shown to have higher gamma-ray and neutron attenuation capabilities when compared to the other glass samples studied. Our outcomes showed that increasing the molar contribution of Al2O3 to the phosphate-based glasses increased not only their transparency but also their gamma-ray and neutron attenuation capacities. It can be concluded that substituting Al2O3 for P2O5 is a functional and monotonic tool for improving the optical, gamma-ray, and neutron attenuation of phosphate-based glasses, which are being evaluated as prospective shielding materials for medical and industrial radiation facilities.
Keywords: Phosphate glasses; Gamma-ray spectroscopy; Neutron; Glass synthesis; Materials Science